Tractostorm 2: Optimizing tractography dissection reproducibility with segmentation protocol dissemination - Rheault, Francois; Schilling, Kurt G.; Valcourt‐Caron, Alex; Théberge, Antoine; Poirier, Charles; Grenier, Gabrielle; Guberman, Guido I.; Begnoche, John; Legarreta, Jon Haitz; Cai, Leon; Roy, Maggie; Edde, Manon; et al. (Human brain mapping, 2022)
The segmentation of brain structures is a key component of many neuroimaging studies. Consistent anatomical definitions are crucial to ensure consensus on the position and shape of brain structures, but segmentations are prone to variation in their interpretation and execution. White‐matter (WM) pathways are global structures of the brain defined by local landmarks, which leads to anatomical definitions being difficult to convey, learn, or teach. Moreover, the complex shape of WM pathways and their representation using tractography (streamlines) make the design and evaluation of dissection protocols difficult and time‐consuming. The first iteration of Tractostorm quantified the variability of a pyramidal tract dissection protocol and compared results between experts in neuroanatomy and nonexperts. Despite virtual dissection being used for decades, in‐depth investigations of how learning or practicing such protocols impact dissection results are nonexistent. To begin to fill the gap, we evaluate an online educational tractography course and investigate the impact learning and practicing a dissection protocol has on interrater (groupwise) reproducibility. To generate the required data to quantify reproducibility across raters and time, 20 independent raters performed dissections of three bundles of interest on five Human Connectome Project subjects, each with four timepoints. Our investigation shows that the dissection protocol in conjunction with an online course achieves a high level of reproducibility (between 0.85 and 0.90 for the voxel‐based Dice score) for the three bundles of interest and remains stable over time (repetition of the protocol). Suggesting that once raters are familiar with the software and tasks at hand, their interpretation and execution at the group level do not drastically vary. When compared to previous work that used a different method of communication for the protocol, our results show that incorporating a virtual educational session increased reproducibility. Insights from this work may be used to improve the future design of WM pathway dissection protocols and to further inform neuroanatomical definitions. Structural connectivity reconstructed using diffusion magnetic resonance imaging tractography can isolate white‐matter pathways using a technique called virtual dissection. Human variability in the interpretation and execution of the virtual dissection causes a measurement error in the digital reconstruction of pathways. This work quantifies the variability of a specific protocol taught using an online course and the impact of repeating the procedures (practices) on variability.